Escola de Teatro e Dança da Universidade Federal Pará: memória e história do ensino do teatro em Belém do Pará (1962-1970) - SANTOS, Ana Maria da Gama (Universidade Federal do Pará, 2019)
Analyzing about the socio-cultural meanings of performing arts teaching at the School of Theater and Dance of the Federal University of Pará (ETDUFPA) is the fundamental point of this research. The study aims to understand the process of actor qualification and the practice of theater teaching in the Paraense Amazon and its historical meanings, through documentary analysis, considering the influences and transformations of theater teaching in the Paraense capital, through ETDUFPA, since its foundation in 1962 until the year 1970, bringing the historical continuity of teaching to the present day. Methodological support involves documentary research, through the survey of official documents produced by the school; and periodicals, photographs and interviews with Carlos Eugênio Marcondes de Moura and Cláudio de Souza Barradas, teacher and former student / founder who participated in the implementation of the Actor Training course, and the trajectory of the School of Theater in the period mentioned above. The theoretical dialogues are made with the studies of memory, based on the reflections proposed by Halbwachs (2013), Nora (1993) and Pollak (1992); with the brazilian / paraense theatrical studies of Bezerra (2013), Faria (2012), Jacobbi (2012), Magaldi (2004), Prado (2008) and Salles (1994). Thus, the current investigation arises from the need to tell this story, because these memories are on the fringes of the studies already done, and the urgency to debate the historical meanings of the establishment of a drama school in Belém, created to qualify actors and actresses of the city. Therefore, this master's research will contribute to the historiography of Brazilian and Pará theater, in dialogue with the field of arts education.